2014
DOI: 10.1016/j.crohns.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility and diagnostic accuracy of faecal calprotectin for IBD at first presentation to gastroenterology services in adults aged 16–50years

Abstract: Background:Distinguishing inflammatory bowel disease (IBD) from functional gastrointestinal (GI) disease remains an important issue for gastroenterologists and primary care physicians, and may be difficult on the basis of symptoms alone. Faecal calprotectin (FC) is a surrogate marker for intestinal inflammation but not cancer.Aim:This large retrospective study aimed to determine the most effective use of FC in patients aged 16–50 presenting with GI symptoms.Methods:FC results were obtained for patients present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 21 publications
4
54
1
3
Order By: Relevance
“…Such a non-invasive peripheral blood biomarker could be used to stratify patients to further intrusive investigations (e.g., colonoscopy). Existing clinically available biomarkers such as faecal calprotectin50 already provide similar utility but are unable to distinguish the two forms of IBD. A different 19-probe methylation-based panel can discriminate CD and UC, potentially facilitating clinical decision-making where the medical and surgical management of the two diseases differ.…”
Section: Discussionmentioning
confidence: 99%
“…Such a non-invasive peripheral blood biomarker could be used to stratify patients to further intrusive investigations (e.g., colonoscopy). Existing clinically available biomarkers such as faecal calprotectin50 already provide similar utility but are unable to distinguish the two forms of IBD. A different 19-probe methylation-based panel can discriminate CD and UC, potentially facilitating clinical decision-making where the medical and surgical management of the two diseases differ.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies illustrate the longitudinal course of fecal calprotectin in the evolution of the disease, and predictive or decision cut-off level differ according to the authors [55,60]. Tibble et al reported that elevated calprotectin level (cut-off level 50 mg/L) showed good predictive value for clinical relapse during the following 12-month period [55].…”
Section: Identification Of Ibd Relapsementioning
confidence: 99%
“…In a large study including 900 patients, Kennedy et al evidenced a sensitivity of 0.97, a specificity of 0.74, an NPV of 0.99, using a threshold of ≥ 50 μg/g for IBD vs. functional disease [60].…”
Section: One or Several Thresholds: That Is The Questionmentioning
confidence: 99%
“…Furthermore, f-Cp is more sensitive and specific for IBD than routinely used systemic inflammatory markers and clinical indices,2–4 6 7 14 17 26–33 and its levels correlate with the degree of neutrophilic infiltration1 4 14 32 as well as endoscopic and histological assessment of disease activity 2 4 5 7 14 27 29–31 33. A study of 895 unselected patients designed to mimic a ‘real world’ undiagnosed patient population reported a sensitivity and specificity of 95% and 75% 17. F-Cp may also be a useful tool for monitoring disease activity and response to therapy and predicting relapse and risk of bowel resection 1–9…”
Section: Introductionmentioning
confidence: 99%